IbM BUDIDAYA LEBAH MADU DENGAN MEMBERDAYAKAN IBU RUMAH TANGGA DI DESA SINGA BANGSA KABUPATEN BOGOR [IbM CULTIVATION OF HONEY BEE BY EMPOWERING HOUSEWIFE IN SINGABANGSA VILLAGE OF BOGOR REGENCY] - Adolf J.N. Parhusip; Abel Gandhy; Rudy Pramono (Universitas Pelita Harapan, 2017)
Singabangsa Village, Tenjo is a village located in Tenjo district, Bogor regency, West Java. The population of Singabangsa village recorded in 2015 was 3,998. 2,002 residents were women who mostly worked as housewives, and they were categorized as underprivileged inhabitant. As the result, a program is needed for the empowerment of women so that standard living of family can be improved. The program carried out was development of honey bee farming business. The objectives of this program are to create a more independent farmer group by empowering women and be able to produce products in accordance to consumers’ preference. This program began in February 2017, and it was divided into several stages. The initial stage was an introductory stage where the participants were explained about basic knowledge regarding honey bee cultivation, bee farm, and its equipment. The later stage was the implementation, where at this stage the participlants were asked to perform the knowledge that has been learned. At the last stage, the participants were given information about processing stages of harvested products. It is hoped that through the stages of socialization program, the Singabangsa’s Honey Bee Farmers group, Tenjo, can manage their honey bee farm independently. Harvesing of honey is done every 3 months with an average production yield of 3 kg honey/colony. The honey products is used for individual needs as a supplementary to family nutrient intake, and they are also packed in a bottle of 250 ml as an addition to family’s income.